2015
DOI: 10.1089/neu.2014.3667
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hippocampal Network Activity afterIn VitroTraumatic Brain Injury

Abstract: Traumatic brain injury (TBI) alters function and behavior, which can be characterized by changes in electrophysiological function in vitro. A common cognitive deficit after mild-to-moderate TBI is disruption of persistent working memory, of which the in vitro correlate is long-lasting, neuronal network synchronization that can be induced pharmacologically by the gamma-aminobutyric acid A antagonist, bicuculline. We utilized a novel in vitro platform for TBI research, the stretchable microelectrode array (SMEA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…Previous studies using other in vitro models have shown that mechanical injury to neurons reduces functional connectivity ( 1315 ). In line with these studies, our results show that single-cell tap injury to multiple neurons reduces overall network connectivity, likely because injury leads to functional uncoupling of a neuron and its neighbors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using other in vitro models have shown that mechanical injury to neurons reduces functional connectivity ( 1315 ). In line with these studies, our results show that single-cell tap injury to multiple neurons reduces overall network connectivity, likely because injury leads to functional uncoupling of a neuron and its neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the large body of evidence supporting a role for astrocytes in establishing neural population synchronization and in protecting against neural degeneration following traumatic brain injury (TBI) ( 12, 13 ), we hypothesized that astrocytes aid in the recovery of neuronal network synchrony, which is disrupted following moderate mechanical injury to neural tissue ( 14, 15 ). To test this hypothesis, we subjected neurons in mixed cultures to targeted injury after mGluR 5 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, neural event activity was detected based on the multi-resolution Teager energy operator (Choi et al, 2006; Kang et al, 2014; Kang and Morrison, 2014, 2015; Patel et al, 2015). Data from each electrode was segregated by anatomical ROI (dentate gyrus [DG], cornu ammonis 1 [CA1], cornu ammonis 3 [CA3]).…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneous network synchronization was also quantified using previously published methods (Kang et al, 2014; Li et al, 2007; Li et al, 2010; Patel et al, 2012; Vogel et al, 2016a). In brief, correlation between neural events was calculated for each electrode pair based upon neural event-timing, where two events occurring within 1.5 ms were considered synchronous, and the total number of events.…”
Section: Methodsmentioning
confidence: 99%
“…To address our hypothesis, we took advantage of a recently developed technology to fabricate stretchable silicone‐based microelectrode arrays (sMEAs). The arrays consist of thermally evaporated thin gold electrodes and leads, patterned and embedded in polydimethylsiloxane (PDMS) membranes, as illustrated in Figure . The intrinsic microstructure of the gold film on PDMS (Figure B) enables reversible deformation of the metallic film to tens of per cent of applied strain .…”
Section: Introductionmentioning
confidence: 99%